Industrial Developments and the Sámi: Ethnopolitical Response to Ecological Crisis in the North - Svensson, Tom G. (Anthropologica, 2022)
In most parts of the Arctic and Subarctic Regions, there is a growing concern among Native peoples about the erosion of their ecological base caused by increasing developments on the part of the dominant, industrialized society. The Sami in northern Fenno-Scandia have long experienced this gradual devastation and presently face a serious ecological crisis. To cope with the exploitation of their land by industrial forestry and hydro-electric developments, the Sami make use of both the legal arena and various political channels.